2022
DOI: 10.1007/s00170-022-10164-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of welding parameters and surface preparation on thin copper–copper sheets welded by ultrasonic welding process

Abstract: Ultrasonic welding is increasingly used in industry. In this paper, the influence of ultrasonic welding parameters (USW) on the joint strength and quality was analysed. The properties of the USW joints depend on many factors. The work focuses on the influence of the technological parameters and the surface properties of welded EN Cu-ETP copper sheets with a thickness of 1 mm. The impact of the process parameters, such as welding time, pressure, vibration amplitude and the surface roughness on the lap shear str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…That is, bonding strength increased with increases in bonded fraction, as shown in the cross-sectional observation. A previous study [21] reports that higher roughness could facilitate a higher degree of plastic deformation to enhance joint strength by mechanical interlocking. With a higher bonding fraction, strength could increase correspondingly (measurement of bonding fraction can refer to Figure S3 in supplementary material, where examples are shown in Figure S3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, bonding strength increased with increases in bonded fraction, as shown in the cross-sectional observation. A previous study [21] reports that higher roughness could facilitate a higher degree of plastic deformation to enhance joint strength by mechanical interlocking. With a higher bonding fraction, strength could increase correspondingly (measurement of bonding fraction can refer to Figure S3 in supplementary material, where examples are shown in Figure S3a).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the welding parameters affecting the formation of bonding areas between Cu sheets, it has been reported that rougher surface combinations yielded better joint strength because rough peaks allowed a higher degree of plastic flow at the contact points [21]. On the other hand, a recent study reports that a smoother surface combination yields a higher strength than a rougher one, which can be attributed to the difference in contact fraction between these two cases [22].…”
Section: Introductionmentioning
confidence: 99%
“…Minitab can create Contour plots with the response variable on the 𝑧-axis and the two control variables on the 𝑥and 𝑦-axes, used to identify optimal values of the predictor variables for a given response variable [15].…”
Section: Data Acquisitionmentioning
confidence: 99%